Advances in Knowledge Discovery and Management Volume 10 - Jaziri, Rakia; Martin, Arnaud; Cornuéjols, Antoine; Cuvelier, Etienne; Guillet, Fabrice (Studies in Computational Intelligence, 2024)
XVI, 129 p. 68 illus., 49 illus. in color.